Respuesta :
the answer:
the main rules of the use of logarithm are
loga[a] = 1
loga[AxB] =loga[A] +loga[B] for all value positive of A and B
loga[A/B] = loga[A] - loga[B] for all value positive of A and B
in our case, log8 4a (b-4/c4)
so it is equivalent to log8 4a + log8(b-4/c4)
and since loga[A/B] = loga[A] l - oga[B] , log8(b-4/c4) =log8(b-4) - log8(c4)
the possible expression:
log8 4a (b-4/c4) = log8 4a + log8(b-4) - log8(c4)
the main rules of the use of logarithm are
loga[a] = 1
loga[AxB] =loga[A] +loga[B] for all value positive of A and B
loga[A/B] = loga[A] - loga[B] for all value positive of A and B
in our case, log8 4a (b-4/c4)
so it is equivalent to log8 4a + log8(b-4/c4)
and since loga[A/B] = loga[A] l - oga[B] , log8(b-4/c4) =log8(b-4) - log8(c4)
the possible expression:
log8 4a (b-4/c4) = log8 4a + log8(b-4) - log8(c4)
The equivalent expression of the given logarithmic expresson is [tex]1+log_8a+log_8 (b-4)-log_8 2c^4[/tex].
The given expression is [tex]log_8 [4a ((b-4)/c^4)][/tex].
Use the basic rules of logarithm to find the equivalent expression.
[tex]log_aa=1\\log(ab)=loga+logb\\log(a/b)=loga-logb\\loga^b=bloga[/tex]
Solve the given expression as,
[tex]log_8 [4a ((b-4)/c^4)]=log_8 [8a ((b-4)/2c^4)]\\=log_8 8+log_8a+log_8 (b-4)-log_8 2c^4\\=1+log_8a+log_8 (b-4)-log_8 2c^4[/tex]
Therefore, the equivalent expression of the given logarithmic expresson is [tex]1+log_8a+log_8 (b-4)-log_8 2c^4[/tex].
For more details, refer to the link:
https://brainly.com/question/23889479